KARAKTER WANITA WIRAUSAHA PADA INDUSTRI KECIL KERUPUK KEMPLANG DI KABUPATEN OGAN ILIR - Oktaviana Miftakhuljanah; Wahyu Budi Priatna; Suharno Suharno (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2016)
Characters that exist in person of self-employment is one of the effort to improve the individual quality so they can improve their business performance. Unique character in entrepreneurial women make them more involved in the processing industry, though the business performance which they run have not increased. The purpose of this study were to identify indicators that determine the psychological character of women entrepreneurs, identify indicators that determine the individual character of women, and analyze the effect of psychological character and the individual character of women entrepreneurs for business performance in small-scale crackers kemplang industry in Ogan Ilir. Data were collected from 120 respondent, which was taken through purposive sampling method. Data were analyzed using the approach of Structural Equation Modeling (SEM). The results showed that psychological character has significant positive effect on business performance. This suggests that the increased on character hardworking, disciplined, risk taker, a visionary, innovative, confident and responsible will improve business performance on a small-scale crackers kemplang industry in Ogan Ilir. So it is necessary to build of character with the involvement of government through policy, training or school of character, as well as capital and facilities, and other infrastructure that support this business activities.